The Impact of Duty Hour Limits on Sleep Quality of Resident: A Cross-sectional Study - Roa’a Jaradat; Amro Lahlouh; Belal Aldabbour; Alaa Saadeh; Mohamed Mustafa (Oman Medical Journal, 2022)
Objectives: Resident physicians are particularly prone to sleep disturbance due to long shift hours and excessive workload. Despite the numerous measures undertaken to improve their wellbeing, it is still unknown if limiting the work shift duration would improve sleep quality. We sought to compare sleep quality, anxiety, and depression before and after implementing duty hour limits. We also aim to evaluate how satisfaction with life is related to sleep quality, anxiety, and depression. Methods: We used a self-reported questionnaire to obtain data about sleep quality, anxiety, and depression using the Pittsburgh Sleep Quality Index and Patient Health Questionnaire-4 (PHQ-4) scales, respectively. Using data from a previous study, we compared those parameters before and after implementing duty hour reduction across several specialties at King Abdullah University Hospital, Jordan. Furthermore, we investigated residents’ life satisfaction using the Satisfaction with Life Scale. Results: One hundred and eighty residents filled the questionnaire (median age = 26.5 years). Males reported higher rates of poor sleep quality while females had higher rates of anxiety and depression. Decreasing the duration of on-call shifts from 32 to 24 hours decreased the prevalence of poor sleep quality from 91.5% to 83.2% (p =0.038), and smoking rates decreased from 30.4% to 12.5% (p < 0.001). More than six on-calls per month were associated with poorer quality of sleep. Night float shifts significantly decreased rates of moderate and severe PHQ-4 scores (p < 0.001). In addition, 63.3% of residents were satisfied with life. Life satisfaction was associated with enhanced sleep quality and lower PHQ-4 scores (p =0.007 and p < 0.001, respectively). Conclusions: Optimizing shift scheduling and duration can positively influence rates of sleep quality, anxiety, depression, and smoking. More interventions should be tackled along with duty hour limits to optimize residents’ life satisfaction.